Factores de riesgo de anemia ferropénica en menores de 5 años hospitalizados. Quito, 2020 - Solange Leticia, Muñoz García, Karol Anthonela, Naranjo Arellano (2020)
Background: Iron deficiency anemia is one of the most important public health problems in the world. Objective: To determine the risk factors for iron deficiency anemia in children under 5 years of age hospitalized at the Carlos Andrade Marin Hospital, during the period January-August 2020. Methodology: descriptive, retrospective, cross-sectional. Population and Sample: 459 patients under five years of age with iron deficiency anemia, who were hospitalized during the study period. Variables: age, sex, origin, socioeconomic level, access to basic services, maternal education, breastfeeding, ablactation, iron supplements, number of daily meals, and nutritional assessment. The information was taken from the medical records and analyzed with the statistical program excel. Results: Prevalence: 21%. age: <1 year (n = 46; 10%); 1-3 years (n = 92; 20%); 4-5 years (n = 321; 70%). Female sex (n = 276; 60%). Urban origin (n = 367; 80%). Medium socioeconomic level and Basic services (n = 459; 100%). Higher maternal education (n = 252; 55%). Exclusive breastfeeding <6 months (n = 298; 65%). Breastfeeding plus formula <6 months (n = 161; 35%). Ablaction ≥ 6 months (n = 367; 80%). Iron supplements (n = 193; 42%). Daily meals: 3-4 times (n = 229; 50%). Nutritional assessment: insufficient height for age (n = 175; 38%). Insufficient weight for age: (n = 358; 78%). Conclusions: Iron deficiency anemia is frequent in countries where the rate of poverty and malnutrition are high, therefore, it requires attention especially in vulnerable groups. Breastfeeding, correct ablactation, and iron supplementation are important in preventing iron deficiency in childhood.